The earth is flat, almost: measuring marketing standardization and profit performance of japanese and U.S. firms - Kustin, Richard Alan (Journal of Global Marketing, 2010)
Globalization has fostered greater interest in all aspects of standardization theory, including the four Ps (product, price, place [distribution], and promotion) of the marketing mix. The study researches the firm's strategy of marketing standardization as it correlates to the firm's profit. Multinational firms from Japan and the United States operating in a global environment were studied in order to correlate marketing standardization to profit performance. The results indicate there is increasing support for a strategy of standardizing marketing mix components and contributing to a firm's profit performance. © Taylor & Francis Group, LLC.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/014-307-214-787-887 tex.type: [object Object]
Keywords: Global marketing; Global strategy; Globalization; Marketing standardization; Profit performance; dept.mkt